اعتمادية التعليم العالي في سورية من منظور التحسين المستمر للجودة - زاهر, بسام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
اعتمدنا في هذا البحث على تقويم الدعائم الأساسية الثلاث الآتية: واقع البحوث العلمية، وإجراءات تحقيق الاعتمادية في التعليم العالي، والخدمات التعليمية. ولقد أشارت نتائج البحث إلى وجود انحرافات جوهرية في اعتمادية التعليم العالي في سورية. ولقد قدم البحث مجموعة توصيات منها: إعطاء الجامعات الاستقلالية الأكاديمية والمالية، وإحداث هيئة وطنية للاعتماد، وإحداث معهد متخصص بالبحوث الجامعية، ورسم سياسة واضحة لتحسين جودة خدمات التعليم العالي، وفتح تخصصات جديدة مطلوبة لسوق العمل. We depended in this research on the evaluation of the following three main supports: the status of scientific research, the procedures of realization of accreditation in higher education, and the instructional services. The results of this research revealed to existence of significant gaps in higher education accreditation in Syria. The research introduced a group of recommendations, including giving the universities financial and academic independence, creating a national forum for accreditation, creating a specialized institution of research, drawing a clear policy to improve the quality of higher education services, and opening the new specializes needed to work market.